A tensile technique for measuring frozen products adhesion strength: Application to stainless steel/frozen milk interaction. (April 2020) - Loho, T.; Leveneur, J.; Davidson, R.; Trompetter, M.M.; Futter, J.; Morel, J.; Archer, R.; Kennedy, J.
Abstract: The adhesion of frozen products such as dairy, water, and juices to industrial metallic surfaces is a major source of inefficiency in the food processing industry. There are different methods developed to quantify ice adhesion strength, but these methods tend to be incomparable due to a combination of tensile and shear force effects. Additionally, these methods usually involve ex-situ freezing which introduced additional experimental errors and prevent cycling of measurements. This paper proposes a new quantitative tensile force technique to characterise the tensile adhesion strength of frozen products to surfaces with less effects from the shear component of force. The in-situ freezing experimental set-up is presented along with case studies performed with commercially available milks in New Zealand to illustrate the benefits and limitations of the method. Results from this technique are not representative of the true ice adhesion strength due to effects of stress concentrations and the use of surfactants. However, this technique shows promise for comparison of the degree of icephobicity for different surfaces. Highlights: A method of tensile ice adhesion strength measurement with in-situ- ice formation was proposed. Method enables comparison of frozen products adhesion strength of different samples. This frozen product adhesion method is designed to be closer to the real-world conditions of Individual Quick Freezing. An increase in the fat content in milk shows increased adhesion strength to the same stainless steel substrate.